Increase of Effectiveness of Management of State Ownership in Saint-Petersburg - Anvar Shavkatovich Sabirov (Управленческое консультирование)
The management of state property is a purposeful, conscious state influences the objects of his property. They also set rules for the possession, use and disposition of such property. State ownership, in the future, should save a significant role, deliverance from profitable enterprises simply unacceptable, as it is necessary to remember about the national security issues. The existence of a strong state and the corporate sector will improve the sustainability of the economy. To ensure this goal required a national program for unification technologically related companies, without cooperation are competitive production impossible.